Two new species of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) from Brazil, with a discussion on the ontogeny of leg setae - Castro, Elizeu B.; Beard, Jennifer J.; Ochoa, Ronald; Bauchan, Gary R.; Feres, Reinaldo J.f. (Zootaxa, 2018)
The Amazon and the Cerrado are the two largest biomes in Brazil, and combined represent nearly 70% of the natural vegetation in the country. Recent surveys of the mite fauna present in these two biomes have revealed a great number of new species. In this paper, we describe the adult females, deutonymphs, protonymphs, larvae and eggs of two new species of Tenuipalpidae (Trombidiformes: Tetranychoidea), Tenuipalpus protium sp. nov., collected on Protium heptaphyllum (Burseraceae), and Tenuipalpus kitajimai sp. nov., collected on an unidentified plant of the family Sapindaceae, from the Cerrado and the Amazon Rainforest, respectively. Females of these two new species bear two distinct cuticular crests on the dorsal opisthosoma, one transverse crest anteriorly and one longitudinal crest mesally. The ontogenetic changes in the idiosomal and leg chaetotaxy of all stages are presented for both species. Adult males are not known for either species.